Concept Design 2 : Works from seven Los Angeles entertainment designers and seventeen guest designers - Design Studio Press; Gould, Robert; Robertson, Scott, 1966-; Goerner, Mark.; Pugh, Nick.; Clyne, James; Burg, Steve; Page, Neville; Belker, H. (Harald); Bouvier, Nicolas; Church, Ryan.; Cole, Dylan; et al. (Culver City, CA : Design Studio Press, 2006)
Features the work of concept designers: Harald Belker, Steve Burg, James Clyne, Mark Goerner, Neville Page, Nick Pugh, Scott Robertson and guest artists: Nicholas Bouvier, Ryan Church, Dylan Cole, Kasra Farahani, Sean Hargreaves, Khang Le, Warren Manser, Stephan Martiniere, Ed Natividad, Rick O'Brien, Dan Wuarnstrom, Christian L. Scheuerer, Oliver Scholl, Farzad Varahramyan, Mike Yamada, Felix Yoon and Feng Zhu.
Includes index.
Keywords: Computer art -- California -- Los Angeles -- History -- 21st century; Commercial art -- California -- Los Angeles -- History -- 21st century; Fantasy in art; Fantasmes dans l'art.